2007
DOI: 10.1177/156482650702800202
|View full text |Cite
|
Sign up to set email alerts
|

Food-Poverty Status and Food Insecurity in Rural West Lombok Based on Mothers' Food Expenditure Equivalency

Abstract: Background. When the Central Bureau for Statistics (CBS) developed a national food-poverty line for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Although it is possible that households in rural areas are sometimes able to grow and produce some of the foods they consume, evidence suggests that cost is a key determining factor that influences the nature and amount of foods consumed, including fortified foods. This is a consistent observation in studies carried out in different countries and settings …”
Section: Equity In Access To Fortified Maize Flour and Corn Mealsupporting
confidence: 90%
See 1 more Smart Citation
“…Although it is possible that households in rural areas are sometimes able to grow and produce some of the foods they consume, evidence suggests that cost is a key determining factor that influences the nature and amount of foods consumed, including fortified foods. This is a consistent observation in studies carried out in different countries and settings …”
Section: Equity In Access To Fortified Maize Flour and Corn Mealsupporting
confidence: 90%
“…Access to fortified foods may also be hindered by the low purchasing power of the individuals who usually need the intervention . Moreover, commercially fortified maize flour and corn meal can be available, but not accessible, owing to slightly increased costs, especially when fortification is voluntary . In some countries, such as Guatemala, rural and low‐income households are more likely to purchase tortillas or other maize‐based foods in local markets rather than purchase industrially processed foods, or to grow their own crop of maize and grind or mill them locally to produce corn masa or flour .…”
Section: Equity In Access To Fortified Maize Flour and Corn Mealmentioning
confidence: 99%
“…Comparisons with other studies in resource-poor settings confirm that our study population has lower food security. In an Indonesian population, Rosalina et al ( 26 ) identified 88·9 % of the severely poor to be food insecure. Pasricha et al ( 27 ) found 52·7 % of a rural Indian population to be food insecure.…”
Section: Discussionmentioning
confidence: 99%
“…Women and girls often eat last, least, and most poorly in private household spaces (Kikafunda & Lukwago, 2005;Musaiger, 1993;Rosalina, Wibowo, Kielmann, & Usfar, 2007;Sasson, 2012), having also least access to the right and resources to eat in public spaces (e.g., in Ethiopia, Scherbaum, 1997). Ethnographic observations reveal retaliatory abuse for cooking transgressions like burning food, preparing too much or too little, or at the wrong time (Ambrosetti, Amara, & Condon, 2013;Beardsworth & Keil, 1997;Burgoyne & Clark, 1984;DeVault, 1991;Dobash, 1979;Schuler, Yount, & Lenzil, 2012;Whitehead, 1994).…”
Section: Methodsmentioning
confidence: 99%